Alterations in lower-leg function and biomechanics in athletes and runners with achilles tendinopathy: a systematic review - Quarmby, A.; Mönnig, J.; Mugele, H.; Henschke, J.; Kim, M. H.; Cassel, M.; Engel, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Achilles tendinopathy (AT) is a persistent injury in athletes, especially for those engaged in repetitive stretch-shortening cycle activities such as running. Clinical risk factors are numerous, but it has been suggested that altered biomechanics might lead to or be associated with the development of AT. No systematic review has been conducted investigating these biomechanical alterations in specifically athletic populations. Therefore, the aim of this systematic review was to synthesise research comparing the lower-limb biomechanics of athletes with AT to asymptomatic controls.